CONGENITAL ATAXIAS: AN INTEGRATIVE LITERATURE REVIEW FROM THE LAST DECADE (2015–2025) - do Nascimento, Cláudio José Alves; Alves, Jamila Silva; Rodrigues, Lilian Najara dos Reis; Iunes, Laura Ribeiro; Carvalho, Crys Darlen Moreira (Seven Editora, 2025)
Congenital ataxias constitute a heterogeneous group of developmental encephalopathies characterized by cerebellar dysfunction present from birth, resulting from genetic, metabolic, or structural alterations. This integrative review analyzed evidence published between 2015 and 2025 in the PubMed, Scielo, Embase, and ScienceDirect databases, addressing genetic, clinical, and therapeutic advances. Sixty-four studies were included, predominantly genetic-molecular (46%), clinical-descriptive (32%), and systematic reviews (22%). The results demonstrated the consolidation of clinical genomics as a first-line diagnostic tool, with etiological elucidation in up to 70% of cases previously classified as idiopathic. The integration of high-resolution neuroimaging and next-generation sequencing (NGS/WES) redefined the diagnosis of congenital ataxias, allowing genotype-phenotype correlations and the identification of specific neuroradiological signatures. From a therapeutic perspective, advances in targeted metabolic supplementation, experimental gene therapies, and noninvasive cerebellar rehabilitation strategies have expanded functional prognosis and quality of life for affected children. It is concluded that congenital ataxias represent a paradigmatic model of precision medicine in child neurology, requiring an interdisciplinary approach and multicenter studies integrating genetics, neurodevelopment, and innovative therapies. DOI: https://doi.org/10.56238/sevened2025.037-029